Analisis Biaya Produksi dan Penentuan Harga Pokok Produksi dalam Pengembangan Agrowisata Berbasis Pengolahan Limbah Daun Manggis di Desa Bulusari - Kinasih, Retno Ayu; Junjunan, Mochammad Ilyas (Universitas Muhammadiyah Gresik, 2025)
Bulusari Village has great potential in developing agrotourism based on the utilization of mangosteen leaf waste, which can improve the village economy and overcome environmental waste problems. This study aims to analyze the production costs and cost of herbal tea products from mangosteen leaf waste to support the development of agrotourism in Bulusari Village. Through the full costing method, the production cost per package is Rp 18,500, with a selling price set at Rp. 24,000 per package. The results of the study indicate that this herbal tea product innovation not only produces profitable economic value, but also opens up new business opportunities and creates jobs for local communities. Thus, the utilization of mangosteen leaf waste can support the sustainability of the village economy and increase the attractiveness of nature-based tourism in Bulusari Village.